MECHANISM OF TAX REGULATION OF ENVIRONMENTAL MANAGEMENT - LABENKO, Oleksandr (Scientific journal «World of Finance», 2024)
Introduction. Ensuring sustainable development is one of the main problems of the modern world. Humanity, in the process of simplifying its life, causes harmful effects on nature and the environment as a whole. In order to reduce the negative impact and achieve economic and social benefits, most countries introduce various environmental taxes, fees and other payments. In today’s realities, they play an important role in generating state revenues, but there is no effective mechanism for their use. Therefore, the analysis of the current state of development of environmental taxation and the mechanism that will ensure the rational use of natural resources are important in today’s conditions. The purpose of the article is to analyze the existing mechanism of budgetary and fiscal regulation of nature use and to justify proposals for its further improvement in accordance with today’s requirements. Methods. The following methods were used in the course of the study and to present its results: analysis, synthesis, generalisation, specification, statistical, graphical. Results. The main features of environmental taxes are determined. The author analyses the share of environmental taxes in the GDP structure of the EU countries and Ukraine. The advantages and disadvantages of environmental taxes are presented. The principles that regulate the institute of environmental taxation are considered. The author’s own vision of building a tax mechanism for regulating environmental management, which includes budgeting and distribution functions, is proposed. Conclusions. Implementation of an effective tax mechanism for regulating environmental management requires careful consideration of specific environmental problems, economic conditions and the regulatory framework of a particular country. The functioning of such a mechanism is rational, which will focus not only on filling the revenue component, but also on their use for environmental protection measures.